Heterosis of the crossbred between Tegal and Mojosari ducks under sub-optimal condition - L. Hardi Prasetyo (Jurnal Ilmu Ternak dan Veteriner, 2007)
Crossbreeding between two different strains or breeds is often done in a livestock production system to take advantage of the heterosis (hybrid vigour) which may resulted from the crossing. The level of heterosis largely depend on the genetic distance betweeen the two parental groups, and is also affected by the environmental condition in which the heterosis would be more significant under less optimal condition. The aim was to evaluate the heterosis level of the crosses between Tegal and Mojosari ducks under stressful environment of low nutritional content (14% protein) in the diet. The experiment was conducted in the animal facilities of the Indonesian Research Institute for Animal production, using 40 Tegal (TT) ducks, 44 Mojosari ducks (MM), 46 crossbreds between Tegal drakes and Mojosari ducks (TM), and 42 crossbreds between Mojosari drakes and Tegal ducks (MT). Results showed that heterosis was not significant for the average age at first laying (AFL) and weight of first egg (WFE), in which AFL of TT (171.8 d) was not significantly different from that of MT (163.4 d) and both were shorter than the AFL of MM (182.3 d) or that of TM (182.8 d). Heterosis also did not exist on egg production to 68 weeks old (EP-68), in which the EP-68 of TT was 141.3 eggs and that of MT was 122.6 eggs, and both were lower than EP-68 of MM (156.8 eggs)  or of TM (154.0 eggs). For egg qualities, heterosis also did not show any significant level and difference between genotypes only existed for the Haugh Unit values. It seems that even under stressful environment heterosis did not exist among crosses between Tegal and Mojosari ducks, and therefore it can be concluded that the crosses between these two breeds will not produce any beneficial effects in a production system under any condition. Key Words: Heterosis, Ducks, Low Protein Diet